Antiviral activity of plant juices and green tea against SARS‐CoV‐2 and influenza virus. (1st March 2022) - Eggers, Maren; Jungke, Peggy; Wolkinger, Volker; Bauer, Rudolf; Kessler, Uwe; Frank, Bruno
Abstract: Respiratory viruses pose a significant threat to global health. They initially infect the naso‐ and oropharyngeal regions, where they amplify, cause symptoms, and may also be transmitted to new hosts. Preventing initial infection or reducing viral loads upon infection might soothe symptoms, prevent dissemination into the lower airways, or transmission to the next individual. Several natural products have well‐described direct antiviral activity or may ameliorate symptoms of respiratory infections. We thus analyzed the potential of plant‐derived products to inactivate respiratory viral pathogens and determined the antiviral activity of black chokeberry ( Aronia melanocarpae [Michx.] Elliott ), elderberry ( Sambucus nigra L.), and pomegranate ( Punica granatum L.) juice, as well as green tea ( Camellia sinensis [L.] Kuntze) on the infectivity of the surrogate‐modified vaccinia virus Ankara, and the respiratory viruses severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), influenza A virus (IAV), and adenovirus Type 5. Black chokeberry and pomegranate juice, and green tea reduced SARS‐CoV‐2 and IAV titers by ≥80% or ≥99%. This suggests that oral rinsing with these products may reduce viral loads in the oral cavity which might prevent viral transmission.